Flooding and health in Australia: a scoping review and coauthorship analysis of published research - Ross Bailie; Geoff Morgan; Jo Longman; Jodie Bailie; Petr Matous; Byron Apelt; Rebecca McNaught; Kanchana Ekanayake (BMJ Open, 2024)
Background Australia is frequently affected by floods, and their severity and frequency are predicted to increase due to the effects of climate change. Over the past decade, there has been an increase in the number of publications reporting on the health impacts of flooding in Australia, but no synthesis of this research evidence has previously been published. The aim of this scoping review is to identify and map publications on the health impacts of flooding in Australia and to describe the networks of researchers contributing to this research.Methods In the study, we applied the scoping review methodology guided by Johanna Briggs Institute and coauthorship network analysis. Searches were conducted in MEDLINE, Embase, PsycINFO, CINHAL, Scopus and Web of Science for all publications up to 31 December 2023. Screening, full-text review and data extraction were completed by two independent reviewers. Coauthor networks were constructed using social network analysis methods.Results 69 publications were included, spanning a 70-year period from 1951 to 2023. The top three health impacts studied were post-traumatic stress disorder (PTSD), distress and child developmental outcomes, with the predominant focus in the past 10 years of recent publications on prenatal maternal stress, child outcomes and mental health impacts. There was minimal focus on socially vulnerable groups and long-term health impacts and few qualitative research studies were reported. Coauthorship analysis showed the primarily disease-specific nature of flood-related research.Conclusion Our review enhances understanding of the research on the physical and mental health impacts of flooding in Australia by identifying the areas of relatively greater research activity, existing research gaps and potential future research priorities. Given the context-dependent nature of flood and other climate-related health impacts, and of mitigation and adaptation responses, we anticipate that our review findings will enhance the understanding of this topic for Australia and other higher-income countries, identifying areas of focus and current research gaps.